Simulation and experimental verification of PID controlled DC/DC buck converter in wind energy conversion system - Mohammed, Hibah; Gheriani, Haneen; Mohamed, Adel; Hammoda, Ahmed; Khalil, Ashraf F.; Khan, Sheroz; Ahmed, Syed Faiz; Ali, Athar (Institute of Electrical and Electronics Engineers Inc., 2018)
DC/DC converters are the key components in small scale wind energy conversion systems. In this paper we investigate the performance of Buck DC/DC converter in wind energy conversion system. The output voltage of the system is regulated using buck PID controller. The voltage is stabilized against the variations in the wind speed. The system has been implemented practically. A simulation has been carried out using Matlab/Simulink. A comparison between the simulation and practical results is presented in the paper. The system shows stable operational performance under different wind speeds.